1978
DOI: 10.1021/bi00607a032
|View full text |Cite
|
Sign up to set email alerts
|

A carbon-13 nuclear magnetic resonance study of the molecular dynamics of methionine-enkephalin and .alpha.-endorphin in aqueous solution

Abstract: Nuclear magnetic resonance (NMR) of 13C is used to probe dynamical properties of [2-[2-13C]glycine]-, [3-[2-13C]glycine]methionine-enkephalin, and a-endorphin. Spin-lattice relaxation times (TI) are reported at 20 MHz for the enriched enkephalin samples as functions of pH, temperature, and concentration. Relaxation times are also reported for enkephalin and a-endorphin containing I3C in natural abundance. The relaxation times are used to monitor the relative flexibility of the carbon atoms in the peptides. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Nevertheless, it is apparent that the Tyr-Gly-fragment of Met-enkephalin, which is likely to be primarily involved in the binding to the receptor [40], has a large degree of freedom toward the rest of the molecule. Our results are in agreement with recent studies of 13C-enriched Met-enkephalin in water by Tancrede et al [31]. They suggest that the two glycine residues are more flexible than the Phe-4 residue, and that the Gly-3 residue is motionally more restricted than the Gly-2 residue.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, it is apparent that the Tyr-Gly-fragment of Met-enkephalin, which is likely to be primarily involved in the binding to the receptor [40], has a large degree of freedom toward the rest of the molecule. Our results are in agreement with recent studies of 13C-enriched Met-enkephalin in water by Tancrede et al [31]. They suggest that the two glycine residues are more flexible than the Phe-4 residue, and that the Gly-3 residue is motionally more restricted than the Gly-2 residue.…”
Section: Resultssupporting
confidence: 94%
“…This first conformational transition at pH 8, which is likely to be determined by the amino group deprotonation, involves Tyr-1 and Gly-2 and could be interpreted as a different orientation of the tyrosyl ring with respect to the Gly-2 a-protons. On the basis of very recently obtained I3C-relaxation times at low concentration [31], a change in the state of aggregation of the peptide can be excluded in water between pH 1.5 and 10.0.…”
Section: Glycine-2 and Glycine-3mentioning
confidence: 99%
“…Since TT1 = ndvli2, T1 can be estimated directly from the linewidths. Activation energies for rotational processes [53] were determined from T , values using Arrhenius expression l/T1 = l/Tl"exp (EIRT),…”
Section: Results and Discussion "0-nmr And Ftir Data On Peptide -Hzo mentioning
confidence: 99%
“…Usually the I3C chemical shift of one amino acid is only slightly affected by its position in the sequence of a peptide. In the case of peptides I and 11, whatever the solvent used, the I3C chemical shifts are very different from those found in Met-enkephalin or Leu-enkephalin [15,16,18,19]. Furthermore, the chemical shift sepa-rations between each corresponding proton or carbon in the cis and truns forms of peptides I and I1 are very large in comparison to those found in thyroliberin (< Glu-His-Pro-NHz) [32].…”
Section: Resultsmentioning
confidence: 99%
“…The nuclear Overhauser enhancement effects are only 60 % of the maximal value indicating that, at 68 MHz, the relaxation occurs outside the 'extreme narrowing limit' (ohf I 1). For peptides of the size of I, several studies have shown that rotational diffusion is highly anisotropic whatever the conformation (extended or folded) adopted by the peptide [18,40]. However, despite these limitations, several very interesting conclusions can be made.…”
Section: I3c Relaxation Measurementsmentioning
confidence: 99%